The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/2158244021994554
|View full text |Cite
|
Sign up to set email alerts
|

Urban and Spatial Planning: Pragmatic Considerations for Plan Implementation Improvements (A Case Study of the City of Bor)

Abstract: The main task of planning documents is to achieve maximal rationality in the use of space, spatial resources, and balanced territorial development. The preparation of plans is regulated by a legislative framework, which embraces multiple phases and stakeholders. In a perfect planning process, it would be expected that all the elements are well coordinated and brought to common understanding, but in reality, obstacles and challenges can occur in any of these steps, especially in the implementation phase. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Nevertheless, instead of directing energy towards green city policy development, changes in the thinking paradigm, and improvement of a participative approach that would inspire citizens to get involved in decision-making, the government of the City of Belgrade seems to have empowered high-handedness in decision-making, excluded citizens from the processes, and provoked them and professionals in urban development to engage against the city when it comes to projects that have an irreversible impact on the environment and cultural heritage (e.g., interfering with the recognizable city skyline by building multistorey buildings at the riverbanks, attempting to build a cable car infrastructure from the historical Kalemegdan Fortress to New Belgrade by cutting down 150 mature trees, etc.). High-handedness and lack of implementation of planning documents have been seen in other cities in the country, too [103].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, instead of directing energy towards green city policy development, changes in the thinking paradigm, and improvement of a participative approach that would inspire citizens to get involved in decision-making, the government of the City of Belgrade seems to have empowered high-handedness in decision-making, excluded citizens from the processes, and provoked them and professionals in urban development to engage against the city when it comes to projects that have an irreversible impact on the environment and cultural heritage (e.g., interfering with the recognizable city skyline by building multistorey buildings at the riverbanks, attempting to build a cable car infrastructure from the historical Kalemegdan Fortress to New Belgrade by cutting down 150 mature trees, etc.). High-handedness and lack of implementation of planning documents have been seen in other cities in the country, too [103].…”
Section: Discussionmentioning
confidence: 99%
“…Travel decision-making is a complex phenomenon (Nikolić et al, 2021). It is observed that the individual decision-making process for travelers differs based on travel motives, various decisions, context effects and social interactions among travel groups.…”
Section: Travel Decision Makingmentioning
confidence: 99%